Complicity to hegemonic masculinity in D. H. Lawrence's Sons and Lovers - Subrayan, Angelina; Wan Yahya, Wan Roselezam (Australian International Academic Centre, 2016)
Men have long been associated with dominance, strength and confidence and the issue regarding being compliant to the acceptable masculine ideal has always been part of a culture’s social identity. This study focuses on the critical discussion on masculinity studies in the classic fiction of D.H Lawrence. Drawing on narrative data from his novel Sons and Lovers (1913), the study examines how hegemonic masculinity is conformed by the male protagonist, Walter Morel, in his gendered relationship. More specifically, the analysis focuses on how the male character aligns himself with the hegemonically authoritarian philosophy of ‘tough’ masculinity. The effects of social practices and socio-historical context in which Lawrence wrote these novels are also examined. The study utilises Connell’s theory of hegemonic masculinity to explicate Lawrence’s depiction of dominant masculinity through his character. The findings reveal that Lawrence aligns his male protagonist to the dominant role by sanctioning aggressiveness, autonomy and violence.